1995
DOI: 10.1007/bf01837407
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory volume decrease in a renal distal tubular cell line (A6) I. Role of K+ and Cl−

Abstract: Changes in volume of A6 epithelial cells were monitored by recording cell thickness (Tc). The response of Tc to a reduction of the basolateral osmolality from 260 to 140 mosmol/kg was recorded while transepithelial Na+ transport was inhibited by 20 microM amiloride. With Cl--containing bathing media, this osmotic challenge elicited a rapid rise in Tc followed by a regulatory volume decrease (RVD). Substitution of SO4(2-) or gluconate for Cl- markedly reduced the RVD, whereas cells completely maintained their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…In these studies, transwell migration was undisturbed when Cl [29]. Our previous experiments demonstrated that incubation of cells in Cl --free solutions (gluconate-substituted solutions) can deplete intracellular Cl -, resulting in an inhibition of the volume-activated chloride current and a decrease of RVD capability [15].…”
Section: Discussionmentioning
confidence: 95%
“…In these studies, transwell migration was undisturbed when Cl [29]. Our previous experiments demonstrated that incubation of cells in Cl --free solutions (gluconate-substituted solutions) can deplete intracellular Cl -, resulting in an inhibition of the volume-activated chloride current and a decrease of RVD capability [15].…”
Section: Discussionmentioning
confidence: 95%
“…The methods used for this study are described in the accompanying paper [4]. Therefore, we restrict this section to those procedures and features which were not used in that study.…”
Section: Methodsmentioning
confidence: 99%
“…Like many epithelial cells, renal cells are capable of regulating their volume in response to variations in external osmotic pressure (1)(2)(3). Briefly, cells respond to an increase in medium osmolarity by a process referred to as regulatory volume increase, whereas cells respond to the dilution of external medium by a regulatory volume decrease (RVD) 2 (4).…”
mentioning
confidence: 99%
“…Briefly, cells respond to an increase in medium osmolarity by a process referred to as regulatory volume increase, whereas cells respond to the dilution of external medium by a regulatory volume decrease (RVD) 2 (4). A variety of transport pathways have been implicated in both processes and result in rapid water flux across the plasma membrane, which causes cells to recuperate their initial volume correspondingly (5).…”
mentioning
confidence: 99%